Health Deficits and (the Absence of) Popular Mobilization in Brazil - Gupta, Madhvi (Brasiliana: Journal for Brazilian Studies, 2013)
The article explains why Brazil’s popular sectors made claims for health during the 1970s and why they did not do so during the 1990s. I argue that the intervention of “external actors”—better situated individuals and social groups—makes all the difference for popular mobilization. This is because they have the skills and resources to challenge dominant ideas, construct mobilization frames and inspire belief among the popular sectors that their actions can be successful. Health movements emerged in the mid-1970s with the intervention of doctors, medical students and the Catholic Church. During the 1990s, however, these external actors largely retreated from an activist role and took up more routine activities. Based on my research in Sapopemba (São Paulo), I argue that without the engagement of middle-class professionals and progressive Church officials, the popular sectors were caught in a “cognitive trap” so that they did not believe their actions would be successful.